Self-assembly of polydimethylsiloxane structures from 2D to 3D for bio-hybrid actuation. (20th August 2015) - Vannozzi, L; Ricotti, L; Cianchetti, M; Bearzi, C; Gargioli, C; Rizzi, R; Dario, P; Menciassi, A
Abstract: This work aims to demonstrate the feasibility of a novel approach for the development of 3D self-assembled polydimethylsiloxane structures, to be used as engineered flexible matrices for bio-hybrid actuation. We described the fabrication of engineered bilayers, organized in a 3D architecture by means of a stress-induced rolling membrane technique. Such structures were provided with ad hoc surface topographies, for both cell alignment and cell survival after membrane rolling. We reported the results of advanced finite element model simulations, predicting the system behavior in terms of overall contraction, induced by the contractile activity of muscle cells seeded on the membrane. Then, we tested in vitro the structure with primary cardiomyocytes to evaluate the real bio-actuator contraction, thus validating the simulation results. At a later stage, we provided the samples with a stable fibronectin coating, by covalently binding the protein on the polymer surface, thus enabling long-term cultures with C2C12 skeletal muscle cells, a more controllable cell type. These tests revealed cell viability and alignment on the rolled structures, but also the ability of cells to differentiate and to form multinucleated and oriented myotubes on the polymer surface, also supported by a fibroblast feeder layer. Our results highlighted the possibility of developing 3D rolled PDMS structures, characterized by different mechanical properties, as novel bio-hybrid actuators.